Three-Dimensional Subsurface Structural Modeling of a Geothermal Prospect in Banda-Neira, Central Maluku, Based on GGMPlus Gravity Data - Nafian, Muhammad; Fahmi, Muhammad; Rahma, Farah Aliya; Suciarty A H, Vionna (Universitas Andalas, 2025)
The Banda Island is located at the convergence of three major tectonic plates: the Indo-Australian Plate, the Eurasian Plate, and the Pacific Plate. Banda Neira Island holds significant geothermal potential that can be utilized as an energy resource. Therefore, this study was conducted to investigate the subsurface structure of the geothermal prospect area using the gravity method. In the gravity data processing, derivative analysis results indicate that the Banda Neira geothermal prospect is controlled by multiple fault systems: faults associated with the collapse of the older Banda Neira caldera, as well as local faults confirmed to be reverse faults. In the 3D modeling results, a geothermal reservoir layer is identified with an estimated density of 1.67–1.77 g/cm³, interpreted as a mixture of tuff and minor lava. The reservoir is predominantly water-filled, inferred from its relatively low density, and is located at depths of approximately 150–700 meters. In the second slicing profile, oriented north-south, a cap rock layer is observed at depths of 0–300 meters from the measurement point, with a density of 1.67–1.77 g/cm³, overlying a volcanic reservoir layer found at 200–700 meters depth, with higher densities ranging from 3.57–3.67 g/cm³.